Multiple And Single Haar Classifier For Face Recognition - Subari, Go Frendi Gunawan, (PROCEEDING IC-ITECHS 2014, 2014)
Haar-Classifier is a well-known tool for face detection in an image. Open-CV libraryalready provide a class for Haar-Classifier implementation. However, one significant problem in face detection is tilt-face-pose recognition. In this paper, we will discuss about two different solutions to overcome the problem. The solutions are written in Python which has a very simple  syntax.  The  first  solution  is  using  multiple  classifier.  Each  of  them  is  trained  to recognize face with different rotation-degrees. The second solution is using single classifier to recognize many face image which have been rotated by different angles.